Use of ITK in Animal Management by Maldharis in Banni Area of Kachchh (Indian Journal of Animal Production and Management, 2024)
The present investigation was conducted in  the Banni area of Kachchh during 2008 to 2012,  which is a vast grazing land spread on the 3847 sq  km area. The main source of livelihood in the region  is rearing of livestock, handicraft and contract based animal grazing system. While the education  level of Maldharis is 26.50% and lower than national  average, their use of ITK in restraining of animals  and conservation of natural resources is unique.  Various restraining tools used by them are Dan and  Nunjan, Vano / Bagari, Pavro, Kutopado, Ango  Mochi and Bundho. They also use “kudo” in goat  and “Dan” to restrain the movement of camel for  grazing and “Bagari” to protect the camel from  suckling by the calf. The use of psychological tools  like voice produced by different size of bells (mutter  or matri) and keeping all the animals in the herd  intact during grazing either during day or night hours  without any human assistance is the best example  of management of animals on the scientific  principles. Similarly, harvesting and conservation of  rain water in the “Khuriya” is also a unique example  of conservation of natural resources. They allow  their buffaloes in the dry pond which prevent heat  stress and also protection from mosquitoes. They  use Khurjadi for transportation of small ruminants,  “Dambh” for identification of animals and for  housing the calves under the tree shade by making  the enclosure called as “Vado.” These techniques  are based on scientific principles and have very  good impact on animal management.
Keywords: Maldharis; Banni grassland,; Kachchh,; ITK; animal management; psychological tools